Genetic characterization of a novel recombined porcine reproductive and respiratory syndrome virus 2 among Nadc30‐like, Jxa1‐like and TJ‐like strains. Issue 3 (5th December 2020) - Zhao, Jun; Zhu, Ling; Huang, Jianbo; Yang, Zexiao; Xu, Lei; Gu, Sirui; Huang, Yao; Zhang, Rubo; Sun, Xiangang; Zhou, Yuancheng; Xu, Zhiwen
Abstract: Porcine reproductive and respiratory syndrome (PRRS) is one of the most economically devastating viral diseases in the global pig industry, including China. Recently, we successfully isolated a porcine reproductive and respiratory syndrome virus (PRRSV) from lung tissue and peripheral blood of piglets at a farm from Dujiangyan in Sichuan, China, and named it the DJY‐19 strain. The full‐length genome sequence of DJY‐19 shared 86.8%–94.1% nucleotide similarity with NADC30‐like and NADC30 PRRSV strains. We compared the open reading frame (ORF) 5 gene of DJY‐19 with 34 PRRSV strains from Genbank. Phylogenetic analysis showed that DJY‐19 clustered with NADC30 strains, characterized by a predicted 131‐amino‐acid deletion in the nonstructural protein (NSP) 2. The results of homology analysis showed that the homology between DJY‐19 and NADC30 (JN654459.1) strains was the highest (95.9%), whereas homology with other domestic strains was lower (80.9%–92.6%). Furthermore, we identified four recombination breakpoints in the DJY‐19 genome; they separated the DJY‐19 genome into four regions. The 8106–9128 nucleotide (nt) region of DIY‐19 was highly similar to the TJ strain, and the 12106–12580 nt region of DIY‐19 was highly similar to the JXA1‐R strain. Our findings demonstrate that DJY‐19 arose from the recombination of North America NADC30 strain and TJ strain and JXA1‐R in China. The application of multiple attenuated vaccine strains has led to complex recombination of PRRSV strains in China. This study provides a theoretical basis for making a more reasonable PRRS virus control and prevention strategy. Abstract : We successfully isolated a porcine reproductive and respiratory syndrome virus (PRRSV) from lung tissue and peripheral blood of piglets at a farm from Dujiangyan in Sichuan, China, and named it the DJY‐19 strain. The full‐length genome sequence of DJY‐19 shared 86.8%–94.1% nucleotide similarity with NADC30‐like and NADC30 PRRSV strains.Our findings demonstrate that DJY‐19 arose from the recombination of North America NADC30 strain and TJ‐like strain and Jxa1‐like in China.